A new distributional record for the Martin del Campo’s Arboreal Alligator Lizard (Abronia martindelcampoi) with comments on the biogeography of arboreal Alligator-lizards in the Sierra Madre del Sur, Mexico - Thalia E. Cruz-Machuca (Taylor & Francis Group, 2021)
Alligator lizards of the genus Abronia are a clade of arboreal and terrestrial squamates distributed throughout much of the highlands of Mexico and Central America. Here, we report a new record of the Mexican endemic A. martindelcampoi that represents the easternmost limit of the species and the lowest known elevational record. We briefly discuss the biogeographical hypotheses that have been proposed in the past concerning this and other related genera.